2017
DOI: 10.3390/ijms18020336
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Nanoparticle-Induced Macrophage Polarization and Reprogramming Research

Abstract: Macrophages are vital regulators of the host defense in organisms. In response to different local microenvironments, resting macrophages (M0) can be polarized into different phenotypes, pro-inflammatory (M1) or anti-inflammatory (M2), and perform different roles in different physiological or pathological conditions. Polarized macrophages can also be further reprogrammed by reversing their phenotype according to the changed milieu. Macrophage polarization and reprogramming play essential roles in maintaining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(134 citation statements)
references
References 58 publications
4
122
0
1
Order By: Relevance
“…Research groups have also shown that within the tumor microenvironment, liposomes can polarize tumor-associated macrophages (TAMs) [107][108][109]. The reprogramming of classically activated (M1) TAMs, which have a role in eradicating tumor cells in their early stages, to alternatively activated M2-like TAMs has been shown to promote tumor growth and metastasis, as shown in Figure 2 [110,111]. In an orthotopic ovarian carcinoma (ID8-VEGF-GFP) mouse model, La-Beck et al showed that empty liposomes increased tumor volume by over 3-fold and doubled the number of metastatic sites, compared to the vehicle control [107].…”
Section: Interactions With the Mononuclear Phagocyte Systemmentioning
confidence: 99%
“…Research groups have also shown that within the tumor microenvironment, liposomes can polarize tumor-associated macrophages (TAMs) [107][108][109]. The reprogramming of classically activated (M1) TAMs, which have a role in eradicating tumor cells in their early stages, to alternatively activated M2-like TAMs has been shown to promote tumor growth and metastasis, as shown in Figure 2 [110,111]. In an orthotopic ovarian carcinoma (ID8-VEGF-GFP) mouse model, La-Beck et al showed that empty liposomes increased tumor volume by over 3-fold and doubled the number of metastatic sites, compared to the vehicle control [107].…”
Section: Interactions With the Mononuclear Phagocyte Systemmentioning
confidence: 99%
“…Cytoskeletal staining showed that ACP NPs reported that nano-porous microstructures mediate osteogenesis by modulating the osteo-immune response of macrophages [34] . An immune microenvironment induced by Cu-MSNs led to robust osteogenic differentiation of BMSCs via the activation of the oncostatin M (OSM) pathway [24] . The surface chemistry and nano-topography scale modulated the macrophage-related osteo-immune environment by changing the expression levels of inflammatory cytokines, osteoclastic activities, and osteogenic, angiogenic, and fibrogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Such findings are of key importance demonstrating ENMs improved capability (vs. their bulk counterparts) to reach and directly interact with APCs with a potential to modulate and compromise normal and optimal cellular functions. Indeed, previous evidence has demonstrated the capacity of ENMs to modulate the function of APCs including perturbation of their polarity which is critical particularly in the context of inflammatory disease and type I allergic hypersensitivity reactions (63)(64)(65).…”
Section: Interaction With Antigen Presenting Cells (Apcs)mentioning
confidence: 99%